Facilitating Conditions of Saudi Arabia – Israel Normalization in 2015-2018 - Maryam Jamilah; Hafizh Ulya Fikra; Zulkifli Harza (Journal of Diplomacy and International Studies, 2019)
Since 2017, there have been several events that indicate the closeness of relations between the Saudi Arabia and Israel. One of the most significant proof was a statement from Muhammad bin Salam in an interview in The Atlantic stating that Israel had rights to their land. The improvement in relations between Israel and Saudi Arabia has come under fire from many parties such as Hezbollah and Palestine. This research aims to analyze the conditions that facilitate Saudi Arabia’s normalization toward Israel in 2015-2018 with desecuritisation theory based on Bezer Coskun observations of Copenhagen School security analysis. This research is a qualitative research using secondary data as its sources. Researcher used desecuritisation variables that were used by Bezer Coskun on his previous research regarding Palestine and Israel in 2009. Those four variables are, 1)The change in the language to define previously securitized issue, 2) Position of the desecuritising actor and the relation between desecuritising actor and audience, 3) Conditions that point out the necessity for desecuritisation. Researcher found that condition that facilitates Saudi-Israel normalization are Muhammad bin Salam as desecuritisation actor and necessity of Israel’s assistances in realization of Saudi Vision 2030 and Iran power raising in Middle East region after Arab Spring 2011.